Case of resected multiple hepatocellular adenomas in a young man with severe obesity - Kentaro Oji; Takeshi Urade; Yoshiteru Iwatani; Katsuhide Tanaka; Hirotaka Hirano; Tsuyoshi Sanuki; Masaru Tomita; Yuki Yamamoto; Yoh Zen; Daisuke Kuroda (Surgical Case Reports)
Abstract Background Hepatocellular adenoma (HCA) is a rare liver tumor that has the potential for rupture and malignant transformation. Here, we report a case of multiple hepatocellular adenomas (HCAs) that were treated by surgical resection. Case presentation An 18-year-old man was admitted to our hospital with proteinuria. His height was 176.5 cm, weight was 126 kg, and body mass index was 40 kg/m2. A liver tumor was incidentally found on abdominal ultrasonography. Contrast-enhanced computed tomography and gadoxetic acid-enhanced magnetic resonance imaging revealed three hepatic tumors that were 68 mm, 16 mm, and 9 mm in segments 3/4, 8, and 1, respectively. A percutaneous needle biopsy of the largest tumor was performed, the diagnosis of unclassified type HCA was made, and laparoscopic partial liver resection was performed of all three. The postoperative course was uneventful, and the patient was discharged 12 days later. An immunohistochemical examination revealed positivity for serum amyloid A protein, no decrease in fatty acid-binding protein, and negativity for β-catenin, glutamine synthetase, and cytokeratin 7. Therefore, these tumors were diagnosed as inflammatory type HCAs. Conclusions We reported an extremely rare case of multiple resected HCAs in a young, obese Japanese man. Our findings suggest that HCA should be considered in the differential diagnosis of liver tumor in obese patients. Further studies that consider clinical and molecular risk factors are required to establish individualized treatment plans for HCA in obese patients.